Pengembangan Aplikasi Berbasis Web untuk Pemesanan Jasa Sablon Pakaian - Tiffani Maria Bernadetta; Arnold Aribowo (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2020)
Clothing is one of the necessities that every individual needs to fulfill. Everyone can buy clothes to fulfill their needs. The ready-to-wear apparel business has helped consumers to meet their needs. In addition to apparel business, screen printing business is in demand because it can meet the needs of consumers more specifically in terms of design, color, size, and quantity. The process of ordering screen printing clothes is generally done in two ways; customers come directly to the store, and customers place orders through WhatsApp. Orders made by coming to the store become less efficient because customers must spend their time to come to the store directly to make purchases. Orders made through WhatsApp also have obstacles for sellers when chats from incoming customers are excessive, so it is difficult to record incoming orders.This research was made using a waterfall system development method and developed using PHP programming language with CodeIgniter framework. System modeling in this study uses use case diagrams, activity diagrams, class diagrams and entity relationship diagrams. The result of this research is a web-based application that can be used to support and facilitate the sales transactions and purchase of ready-to-wear printed clothing and custom printed clothing.